Associations of Racial and Ethnic Category, Age, Comorbidities, and Socioeconomic Factors on Concordance to NCCN Guidelines for Patients With High-Risk Biliary Tract Cancers After Surgery - Huang, Lauren F.; Hong, Augustine; Cioffi, Gino; Alahmadi, Asrar; Tang, Tin-Yun; Ocuin, Lee M.; Patil, Nirav; Bajor, David L.; Saltzman, Joel N.; Mohamed, Amr; Selfridge, Eva; Webb Hooper, Monica; et al. (Frontiers in Oncology, 2022)
Background Biliary tract cancers (BTC) have a limited prognosis even for localized cancers, emphasizing the importance of multidisciplinary management. NCCN guidelines recommend adjuvant chemotherapy (CT) +/- radiotherapy (RT) for high-risk disease. We analyzed the association between racial and ethnic category along with other demographic factors and concordance to NCCN guidelines among patients following surgery for high-risk BTC. Methods Subjects were identified from the National Cancer Database (NCDB) for BTC patients who underwent surgery and found to have metastatic lymph nodes (LN+) or positive surgical margins (M+) from 2004 to 2015. We defined concordance to NCCN guidelines as receiving surgery + CT +/- RT and non-concordance to the guidelines as surgery +/- RT. Descriptive studies and multivariate logistic regression analysis was performed. Results A total of 3,792 patients were identified with approximately half being female (55.4%) and between the ages of 50-69 (52.8%). Most were White (76.3%) followed by Black (10.6%), Hispanic (8.5%), and Asian (5.3%). The BTC included extrahepatic cholangiocarcinoma (CCA) (48.6%), gallbladder cancer (43.5%), and intrahepatic CCA (7.9%). Most patients had an M- resection (71.9%) but also had LN+ disease (88.0%). There were no significant differences between racial groups in disease presentation (histological grade, tumor stage) and surgical outcomes (LN+, M+, hospital readmission, and 90 day post-surgery mortality). Hispanic patients as compared to White patients were less likely to be insured (85.7% vs 96.3%, p<0.001) and less likely to be treated at an academic facility (42.1% vs 52.1%, p=0.008). Overall, almost one-third (29.7%) of patients received non-concordant NCCN guideline care with Hispanic patients having the highest proportion of non-concordance as compared to Whites patients (36.1% vs 28.7%, p=0.029). On multivariate analysis, Hispanic ethnicity (HR=1.51, 95% CI: 1.15-1.99) remained significantly associated with non-concordance to NCCN guidelines. Conclusion This study indicates that Hispanic patients with high-risk BTC are significantly less likely to receive NCCN-concordant treatment in comparison to White patients. More research is needed to confirm and understand the observed disparities and guide targeted interventions at the system-level.